The Contribution of John Rawls’ and H. A. R. Tilaar's Thoughts to the Development of Multicultural Christian Religious Education in the Industrial Revolution 4.0 Era - Momongan, Christy Monica (International Journal of Education, Information Technology, and Others, 2024)
In the formation of a healthy multicultural society, efforts must be systematic, pragmatic, and continuous. One of the most strategic steps in this regard is through multicultural education conducted by all educational institutions. Multicultural education is also a process of developing the full potential of individuals who appreciate their plurality and heterogeneity as a consequence of cultural, ethnic, tribal, and religious diversity. Sometimes, these differences can trigger conflicts. Therefore, multicultural-based Christian religious education is present to minimize such conflicts. The aim of this research is to analyze the concepts of John Rawls and H.A.R. Tilaar regarding multicultural education and how the implementation of multicultural-based Christian religious education is applied in the era of Industry 4.0. This research uses a literature study method with a qualitative approach. The final result of the research is that multicultural Christian religious education plays a very important role in developing patterns to build justice and peace based on multiculturalism as a means to build trust, mutual respect, giving and receiving, and adapting to each other based on local wisdom and culture.